Beyond the spot - George, Duncan (Henry Stewart Talks, 2008)
A brief history of non spot advertising on radio, An explanation of the characteristics of the medium that make it appropriate for this type of business, Some real life examples of how advertisers have used the medium with non spot campaigns, Advice on best practice, A look to the future
Archived at 2022/03/17